A modified sodium titanate negative electrode material, a negative electrode for a sodium ion battery, and a sodium ion battery

By embedding lithium titanate in sodium titanate and uniformly dispersed and adhered, the modified sodium titanate negative electrode material is formed, and the problem of insufficient performance of existing sodium ion battery negative electrode materials is solved, achieving higher first-time Coulomb efficiency and longer Cycle life and more linear charge and discharge curves.

CN115395005BActive Publication Date: 2025-02-18ANQING CHAOREN ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210877590.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-25
Publication Date
2025-02-18
Estimated Expiration
2042-07-25

AI Technical Summary

Technical Problem

The first time the existing sodium ion battery negative electrode materials have low efficiency, insufficient tap density and short cycle life, making it difficult to meet the demand for battery performance in social development.

Method used

By embedding lithium titanate in sodium titanate and using surfactant to uniformly disperse and adhere to the surface of sodium titanate, a modified sodium titanate negative electrode material is formed, and its tap density and performance stability are improved.

Benefits of technology

It significantly improves the first Coulomb efficiency and tap density of sodium ion batteries, extends the cycle life of the battery, and makes the charge and discharge curve more linear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003762844610000071
    Figure BDA0003762844610000071
  • Figure HDA0003762844620000011
    Figure HDA0003762844620000011
  • Figure HDA0003762844620000021
    Figure HDA0003762844620000021
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion batteries, and discloses a modified sodium titanate negative electrode material, a sodium ion battery negative electrode, and a sodium ion battery. The present invention utilizes the affinity between anionic surfactants and cationic surfactants to make lithium titanate uniformly dispersedly attached to the surface of sodium titanate, and the sodium titanate is modified to obtain a modified sodium titanate negative electrode material. The material is applied to the sodium ion negative electrode, which greatly improves the energy density of sodium titanate as a battery negative electrode and improves the performance stability of the battery. At the same time, the sodium ion battery containing the modified sodium titanate negative electrode material has a good cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a modified sodium titanate negative electrode material, a sodium ion battery negative electrode and a sodium ion battery. Background Art

[0002] The core raw materials of lithium batteries are lithium carbonate and lithium hydroxide, but the content of lithium in the earth's crust is low and lithium mining is difficult. With the widespread application of lithium batteries, such as electric vehicles, mobile phones, laptops, power tools, electric two-wheeled vehicles, energy storage and other special vehicle batteries, the contradiction between lithium supply and demand is prominent, the price of lithium carbonate is rising, and the cost of lithium batteries is also increasing sharply. Therefore, it is urgent to find a replacement battery for lithium batteries.

[0003] Sodium and lithium have similar properties, and sodium-ion batteries can be a good supplement to lithium-ion batteries. The advantage of sodium ions is that the raw material for the positive electrode, sodium, is abundant in the earth's crust, easy to obtain, and inexpensive. However, there are also problems that need to be solved in the manufacture and application of sodium-ion batteries.

[0004] For example, the current sodium ion battery negative electrode generally uses coal-based or biomass amorphous hard carbon, which has the following problems: (1) Amorphous carbon has a low first coulombic efficiency due to its low degree of graphitization; (2) The influence of precursors and sintering temperature leads to low true density and tap density; (3) The sodium embedding mechanism of hard carbon is unclear, which causes great interference to the negative electrode film formation and electrolyte development. For example, the Chinese patent with authorization announcement number CN104600271B and authorization announcement date of February 22, 2017 provides a method for preparing a sodium ion battery sodium titanate / graphene composite negative electrode material. The sodium titanate / graphene composite negative electrode material provided by the patent has a low first coulombic efficiency of only 320mAh / g.

[0005] Therefore, more sodium-ion battery technologies are needed to provide sodium-ion batteries with higher first coulombic efficiency, long cycle life and excellent rate performance to meet the increasingly progressive social development of mankind and to meet the needs of people's daily lives. Summary of the invention

[0006] In order to solve the above-mentioned technical problems of improving the first coulomb efficiency and tap density of sodium ions and increasing the cycle life, the present invention provides a modified sodium titanate negative electrode material, a sodium ion battery negative electrode and a sodium ion battery. The present invention modifies the sodium titanate by embedding lithium titanate in the sodium titanate, thereby greatly improving the tap density of the sodium titanate as the battery negative electrode and improving the performance stability of the battery. The sodium ion battery containing the modified sodium titanate negative electrode material has a good cycle life.

[0007] The specific technical scheme of the present invention is:

[0008] On the one hand, the present invention provides a modified sodium titanate negative electrode material, which comprises the following components in parts by weight: 100 parts of modified sodium titanate, 40-50 parts of N-methylpyrrolidone, 3-4 parts of conductive agent, 1-2 parts of sodium carboxymethyl cellulose, 0.5-1 parts of binder, and 0.1-0.2 parts of anhydrous ethanol. Among them, the raw materials of modified sodium titanate include: sodium titanate, lithium titanate, sodium dodecylbenzene sulfonate, octadecyl ammonium chloride, and deionized water. Preferably, the particle size of sodium titanate is not greater than 15 μm, and the particle size of lithium titanate is not greater than 5 μm. Lithium titanate is uniformly dispersed and attached to the surface of the sodium titanate.

[0009] Lithium titanate is embedded in the structure of sodium titanate, and the sodium titanate is modified to increase the tap density of sodium titanate as an electrode material, thereby increasing the unit capacity of the electrode. The present invention enables lithium titanate to be evenly dispersed and attached to the surface of sodium titanate through the action of a surfactant. Specifically, a wet grinding method is adopted, and the surfaces of sodium titanate and lithium titanate are firstly wrapped with anionic surfactants and cationic surfactants respectively, and then the affinity of the surfactant is utilized to make lithium titanate evenly dispersed and attached to the surface of sodium titanate under high-speed stirring to obtain a modified sodium titanate negative electrode material. In the negative electrode prepared using the modified sodium titanate negative electrode material, when the electrode potential is high during the charging process, the lithium titanate on the surface can also compensate for the sodium insertion, which greatly slows down the problem of polarization of the sodium titanate reaction and prolongs the cycle life of the battery. At the same time, due to the compensatory sodium insertion effect of lithium titanate, the charge and discharge curve of the negative electrode is more linear.

[0010] Specifically, the preparation method of the modified sodium titanate is as follows:

[0011] (a) Sodium titanate, sodium dodecylbenzene sulfonate and deionized water are mixed and stirred at a mass ratio of 20:4-5:35-40 at 25-30°C, and then put into a high-speed ball mill. One cycle is "grinding for 1-2 minutes and resting for 10-15 seconds". After 10-12 cycles of grinding, the mixture is dried and dispersed to obtain particles A with a particle size of no more than 15 μm. Through the external physical force of ball milling, after drying, particles A are formed in which sodium dodecylbenzene sulfonate is uniformly attached to the surface of the sodium titanate structure. Since high-speed ball milling generates heat, ball milling in an intermittent manner is more conducive to the formation and stability of the structure of particles A.

[0012] (b) At 25-30° C., lithium titanate, octadecyl ammonium chloride and deionized water are mixed and stirred in a mass ratio of 20:4-5:34-38, and then placed in a high-speed ball mill. After 9-11 cycles of grinding with a rest period of 10-15 seconds for 1 cycle, the mixture is dried and dispersed to obtain particles B with a particle size of no more than 5 μm. Through the external physical force of ball milling, after drying, particles B are formed in which octadecyl ammonium chloride is uniformly attached to the surface of the lithium titanate structure. Since high-speed ball milling generates heat, intermittent ball milling is more conducive to the formation and stability of the structure of particle B.

[0013] (c) Mixing particles A, particles B and deionized water at a mass ratio of 5-6:3-4:100 at 35-45° C., stirring at a dispersion line speed of 35-40 m / s for 40-50 min, and then drying and dispersing to obtain modified sodium titanate.

[0014] Preferably, the grinding rate in step (a) is 700-800 r / min.

[0015] On the other hand, the present invention provides a method for preparing a negative electrode of a sodium ion battery containing the above-mentioned modified sodium titanate negative electrode material, which comprises the following steps:

[0016] (1) mixing sodium carboxymethyl cellulose and N-methyl pyrrolidone at 35 to 55° C., stirring at a dispersion line speed of 10 to 20 m / s until a mixed liquid becomes clear and transparent; adding a conductive agent to the mixed liquid at 20 to 35° C., stirring at a dispersion line speed of 15 to 30 m / s for 2 to 5 hours to obtain a primary slurry;

[0017] (2) adding the modified sodium titanate material to the primary slurry at 20-35° C., stirring at a dispersion line speed of 35-40 m / s for 2.5-5.5 h, and then adding a binder and anhydrous ethanol and stirring for 1-3 h to obtain a slurry containing the modified sodium titanate material;

[0018] (3) The obtained slurry containing modified sodium titanate material is mixed at a rate of 100 to 200 g / m 2 The density is evenly coated on the current collector, and after roll pressing, the negative electrode of the sodium ion battery is obtained by die cutting.

[0019] Preferably, in step (2), the fineness of the slurry is not greater than 15 μm.

[0020] Preferably, in step (3), the material of the current collector is one of aluminum foil, copper foil and titanium foil.

[0021] Preferably, in step (3), the compaction density of the roller pressing is 1.6 to 2.4 g / cm 3 .

[0022] Preferably, the conductive agent is one or more of acetylene black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene. The binder is one or more of polyvinylidene fluoride, sodium alginate, polyacrylic acid, polytetrafluoroethylene, acrylonitrile copolymer, polyethylene oxide, and styrene-butadiene rubber.

[0023] In addition, the present invention also provides a sodium ion battery, the raw materials of which include modified sodium titanate negative electrode material.

[0024] Compared with the prior art, the present invention has the following technical effects:

[0025] (1) The method of the present invention uniformly disperses lithium titanate and attaches it to the surface of the sodium titanate structure through the affinity of anionic surfactants and cationic surfactants, thereby modifying the sodium titanate, increasing the tap density of the sodium titanate as a negative electrode of the battery, and improving the performance stability of the battery.

[0026] (2) The present invention uses modified sodium titanate negative electrode material to prepare the sodium ion battery negative electrode, which has a relatively linear charge and discharge curve.

[0027] (3) In a sodium ion battery containing the modified sodium titanate negative electrode material of the present invention, during the charging process, the sodium titanate on the surface of the negative electrode sheet can compensate for the sodium embedding, which greatly alleviates the problem of sodium titanate reaction polarization and has a longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a charge and discharge curve diagram of the negative electrode of Example 1;

[0029] Figure 2 is a charge and discharge curve diagram of the negative electrode of Example 2;

[0030] Figure 3 is a charge and discharge curve diagram of the negative electrode of Example 3;

[0031] Figure 4 This is a charge and discharge curve diagram of the negative electrode of Comparative Example 1;

[0032] Figure 5 This is the charge and discharge curve of the negative electrode of Comparative Example 2. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the embodiments.

[0034] Example 1

[0035] A modified sodium titanate negative electrode material comprises the following components in parts by weight: 100 parts of modified sodium titanate, 40 parts of N-methyl pyrrolidone, 3 parts of acetylene black, 1 part of sodium carboxymethyl cellulose, 0.5 parts of sodium alginate and 0.1 parts of anhydrous ethanol.

[0036] Preparation of modified sodium titanate:

[0037] (a) At 25° C., sodium titanate with a particle size of 10 to 15 μm, sodium dodecylbenzene sulfonate and deionized water were mixed and stirred in a mass ratio of 20:4:35, and then put into a high-speed ball mill. After 10 cycles of grinding at 700 r / min for 1 min and resting for 10 s, the mixture was dried and dispersed to obtain particles A with a particle size of 6 to 15 μm.

[0038] (b) At 25° C., lithium titanate with a particle size of 1 to 5 μm, octadecyl ammonium chloride and deionized water are mixed and stirred in a mass ratio of 20:5:34, and then put into a high-speed ball mill. One cycle is "grinding at 700 r / min for 1 min and resting for 10 s". After 10 cycles of grinding, the mixture is dried and dispersed to obtain particles B with a particle size of 1 to 5 μm.

[0039] (c) at 35° C., particles A, particles B and deionized water were mixed in a mass ratio of 5:3:100, stirred at a dispersion line speed of 35 m / s for 40 min, and then dried and dispersed to obtain a modified sodium titanate in which lithium titanate was uniformly dispersed and attached to the surface of the sodium titanate.

[0040] Preparation of sodium ion battery negative electrode:

[0041] (1) At 35° C., sodium carboxymethyl cellulose and N-methyl pyrrolidone were mixed, and stirred at a dispersion line speed of 10 m / s until a mixed liquid became clear and transparent; at 20° C., acetylene black was added to the mixed liquid, and stirred at a dispersion line speed of 15 m / s for 2 h to obtain a primary slurry.

[0042] (2) At 20° C., the modified sodium titanate material is added to the primary slurry, and the mixture is stirred at a dispersion line speed of 35 m / s for 2.5 h. Then, sodium alginate and anhydrous ethanol are added and stirred for 1 h to obtain a slurry containing the modified sodium titanate material, the fineness of which is not greater than 15 μm.

[0043] (3) The obtained slurry containing modified sodium titanate material was heated at 100 g / m 2 The density is evenly coated on the aluminum foil at 1.6g / cm 3 After rolling with a compaction density of 1.540 nm, the negative electrode of the sodium ion battery is obtained by die cutting.

[0044] Preparation of sodium ion batteries:

[0045] The sodium-ion battery negative electrode prepared above was stacked with the sodium-based positive electrode, assembled, and injected with NaPF 6 With NaClO 4 After the solution is mixed, it is subjected to formation, aging, evacuation and sealing in sequence to obtain a sodium ion battery containing a modified sodium titanate negative electrode material.

[0046] Example 2

[0047] A modified sodium titanate negative electrode material comprises the following components in parts by weight: 100 parts of modified sodium titanate, 50 parts of N-methylpyrrolidone, 4 parts of conductive graphite, 2 parts of sodium carboxymethyl cellulose, 1 part of polyvinylidene fluoride, and 0.2 parts of anhydrous ethanol.

[0048] Preparation of modified sodium titanate:

[0049] (a) At 30° C., sodium titanate, sodium dodecylbenzene sulfonate and deionized water with a particle size of 6 to 15 μm are mixed and stirred in a mass ratio of 20:5:37, and then put into a high-speed ball mill. One cycle is "grinding at 800 r / min for 1 min and resting for 12 s". After 12 cycles of grinding, the mixture is dried and dispersed to obtain particles A with a particle size of 6 to 15 μm.

[0050] (b) At 30° C., lithium titanate with a particle size of 1 to 3 μm, octadecyl ammonium chloride and deionized water are mixed and stirred in a mass ratio of 20:4:35, and then put into a high-speed ball mill. One cycle is "grinding at 800 r / min for 1 min and resting for 12 s". After 9 cycles of grinding, the mixture is dried and dispersed to obtain particles B with a particle size of 1 to 5 μm.

[0051] (c) at 45° C., particles A, particles B and deionized water were mixed in a mass ratio of 5:4:100, stirred at a dispersion line speed of 40 m / s for 45 min, and then dried and dispersed to obtain modified sodium titanate in which lithium titanate was uniformly dispersed and attached to the surface of the sodium titanate.

[0052] Preparation of sodium ion battery negative electrode:

[0053] (1) At 55° C., sodium carboxymethyl cellulose and N-methyl pyrrolidone are mixed, and stirred at a dispersion line speed of 20 m / s until a mixed liquid becomes clear and transparent; at 35° C., conductive graphite is added to the mixed liquid, and stirred at a dispersion line speed of 30 m / s for 2 h to obtain a primary slurry.

[0054] (2) At 35° C., the modified sodium titanate material is added to the primary slurry, and the mixture is stirred at a dispersion line speed of 40 m / s for 3 h. Then, polyvinylidene fluoride and anhydrous ethanol are added and stirred for 2 h to obtain a slurry containing the modified sodium titanate material, wherein the fineness of the slurry is not greater than 15 μm.

[0055] (3) The obtained slurry containing modified sodium titanate material was heated at 200 g / m 2 The density is evenly coated on the aluminum foil at 2.4g / cm 3 After rolling with a compaction density of 1.540 nm, the negative electrode of the sodium ion battery is obtained by die cutting.

[0056] Preparation of sodium ion batteries:

[0057] The sodium-ion battery negative electrode prepared above was stacked with the sodium-based positive electrode, assembled, and injected with NaPF 6 With NaClO 4 After the solution is mixed, it is subjected to formation, aging, evacuation and sealing in sequence to obtain a sodium ion battery containing a modified sodium titanate negative electrode material.

[0058] Example 3

[0059] A modified sodium titanate negative electrode material comprises the following components in parts by weight: 100 parts of modified sodium titanate, 45 parts of N-methylpyrrolidone, 4 parts of graphene, 2 parts of sodium carboxymethyl cellulose, 1 part of acrylonitrile copolymer, and 0.2 parts of anhydrous ethanol.

[0060] Preparation of modified sodium titanate:

[0061] (a) At 28° C., sodium titanate, sodium dodecylbenzene sulfonate and deionized water with a particle size of 6 to 15 μm are mixed and stirred in a mass ratio of 4:1:8, and then put into a high-speed ball mill. One cycle is "grinding at 750 r / min for 2 min and resting for 15 s". After 12 cycles of grinding, the mixture is dried and dispersed to obtain particles A with a particle size of no more than 15 μm.

[0062] (b) At 28°C, lithium titanate with a particle size of 1 to 3 μm, octadecyl ammonium chloride and deionized water were mixed and stirred in a mass ratio of 20:5:38, and then put into a high-speed ball mill. One cycle was "grinding at 750 r / min for 2 min and resting for 15 s". After 11 cycles of grinding, the mixture was dried and dispersed to obtain particles B with a particle size of no more than 5 μm.

[0063] (c) at 40° C., particles A, particles B and deionized water were mixed in a mass ratio of 5:3:100, stirred at a dispersion line speed of 38 m / s for 50 min, and then dried and dispersed to obtain modified sodium titanate in which lithium titanate was uniformly dispersed and attached to the surface of the sodium titanate.

[0064] Preparation of sodium ion battery negative electrode:

[0065] (1) mixing sodium carboxymethyl cellulose and N-methyl pyrrolidone at 45° C., and stirring at a dispersion line speed of 10 m / s until a mixed liquid becomes clear and transparent; adding graphene to the mixed liquid at 30° C., and stirring at a dispersion line speed of 25 m / s for 5 h to obtain a primary slurry;

[0066] (2) adding the modified sodium titanate material to the primary slurry at 30° C., stirring at a dispersion line speed of 38 m / s for 5.5 h, and then adding acrylonitrile copolymer and anhydrous ethanol and stirring for 3 h to obtain a slurry containing the modified sodium titanate material, the fineness of the slurry being no greater than 15 μm;

[0067] (3) The obtained slurry containing modified sodium titanate material was heated at 150 g / m 2 The density is evenly coated on the aluminum foil at 2.0g / cm 3 After rolling with a compaction density of 1.540 nm, the negative electrode of the sodium ion battery is obtained by die cutting.

[0068] Preparation of sodium ion batteries:

[0069] The sodium-ion battery negative electrode prepared above was stacked with the sodium-based positive electrode, assembled, and injected with NaPF 6 With NaClO 4 After the solution is mixed, it is subjected to formation, aging, evacuation and sealing in sequence to obtain a sodium ion battery containing a modified sodium titanate negative electrode material.

[0070] Comparative Example 1 (the difference from Example 1 is that the modified sodium titanate in the negative electrode material is replaced by sodium titanate and lithium titanate) A modified sodium titanate negative electrode material comprises the following components in parts by weight: 62.5 parts of sodium titanate, 37.5 parts of lithium titanate, 40 parts of N-methylpyrrolidone, 3 parts of acetylene black, 1 part of sodium carboxymethyl cellulose, 0.5 parts of sodium alginate, and 0.1 parts of anhydrous ethanol.

[0071] Preparation of sodium ion battery negative electrode:

[0072] (1) At 35° C., sodium carboxymethyl cellulose and N-methyl pyrrolidone were mixed, and stirred at a dispersion line speed of 10 m / s until a mixed liquid became clear and transparent; at 20° C., acetylene black was added to the mixed liquid, and stirred at a dispersion line speed of 15 m / s for 2 h to obtain a primary slurry.

[0073] (2) At 20° C., sodium titanate and lithium titanate are added to the primary slurry and stirred at a dispersion line speed of 35 m / s for 2.5 h, and then sodium alginate and anhydrous ethanol are added and stirred for 1 h to obtain a slurry containing modified sodium titanate material, the fineness of the slurry being no greater than 15 μm.

[0074] (3) The obtained slurry containing modified sodium titanate material was heated at 100 g / m 2 The density is evenly coated on the aluminum foil at 1.6g / cm 3 After rolling with a compaction density of 1.540 nm, the negative electrode of the sodium ion battery is obtained by die cutting.

[0075] Preparation of sodium ion batteries:

[0076] The sodium-ion battery negative electrode prepared above was stacked with the sodium-based positive electrode, assembled, and injected with NaPF 6 With NaClO 4 After the solution is mixed, it is subjected to formation, aging, evacuation and sealing in sequence to obtain a sodium ion battery containing a modified sodium titanate negative electrode material.

[0077] Comparative Example 2 (the difference from Example 1 is that the modified sodium titanate in the negative electrode material is replaced with sodium titanate)

[0078] A modified sodium titanate negative electrode material comprises the following components in parts by weight: 100 parts of sodium titanate, 40 parts of N-methylpyrrolidone, 3 parts of acetylene black, 1 part of sodium carboxymethyl cellulose, 0.5 parts of sodium alginate and 0.1 parts of anhydrous ethanol.

[0079] Preparation of sodium ion battery negative electrode:

[0080] (1) At 35° C., sodium carboxymethyl cellulose and N-methyl pyrrolidone were mixed, and stirred at a dispersion line speed of 10 m / s until a mixed liquid became clear and transparent; at 20° C., acetylene black was added to the mixed liquid, and stirred at a dispersion line speed of 15 m / s for 2 h to obtain a primary slurry.

[0081] (2) At 20° C., the modified sodium titanate material is added to the primary slurry, and the mixture is stirred at a dispersion line speed of 35 m / s for 2.5 h. Then, sodium alginate and anhydrous ethanol are added and stirred for 1 h to obtain a slurry containing the modified sodium titanate material, the fineness of which is not greater than 15 μm.

[0082] (3) The obtained slurry containing modified sodium titanate material was heated at 100 g / m 2 The density is evenly coated on the aluminum foil at 1.6g / cm 3 After rolling with a compaction density of 1.540 nm, the negative electrode of the sodium ion battery is obtained by die cutting.

[0083] Preparation of sodium ion batteries:

[0084] The sodium-ion battery negative electrode prepared above was stacked with the sodium-based positive electrode, assembled, and injected with NaPF 6 With NaClO 4 After the solution is mixed, it is subjected to formation, aging, evacuation and sealing in sequence to obtain a sodium ion battery containing a modified sodium titanate negative electrode material.

[0085] Performance Testing

[0086] The sodium ion batteries prepared in Examples 1 to 3 were subjected to performance tests, and the test results are shown in Table 1. The test method for the -20°C discharge retention rate is: first fully charge the battery to 4.0V at 0.5C current, then discharge to 1.5V after standing at -20°C for 12 hours, and take the ratio of the -20°C discharge capacity to the 20°C discharge capacity to obtain the -20°C discharge retention rate. The test method for the cycle life is: "0.5C fully charged to 4.0V, set aside for 10 minutes, then 1C discharged to 1.5V, then set aside for 10 minutes" Repeat this process once for 1 week, and record the number of weeks when the last capacity retention rate is above 90%.

[0087] Table 1

[0088]

[0089] Data Analysis and Conclusion:

[0090] (1) Compared with Example 1, the energy density of the negative electrode of Comparative Examples 1 and 2 is greatly reduced, showing the superiority of the modified sodium titanate negative electrode material in improving the energy density; the energy density of Comparative Example 1, in which the negative electrode material is a direct mixture of sodium titanate and lithium titanate, is lower than that of Comparative Example 2, in which the negative electrode material is only sodium titanate, indicating that it is not feasible to increase the energy density by directly adding lithium titanate to the original formula, and the way in which lithium titanate plays a role is through the modification of sodium titanate.

[0091] (2) Compared with Example 1, the -20°C discharge retention rate and 3C discharge capacity retention rate of Comparative Examples 1 and 2 are both reduced, indicating that the modified sodium titanate negative electrode material is applied to the negative electrode of the sodium ion battery, which is beneficial to improving the stability of the sodium ion battery.

[0092] (3) It can be seen from Examples 1 to 3 that the sodium ion battery using the modified sodium titanate negative electrode material as the negative electrode has a capacity retention rate of more than 90% after 1580 cycles, while the capacity retention rate of Comparative Example 1 using a direct mixture of sodium titanate and lithium titanate as the negative electrode material and Comparative Example 2 using only sodium titanate as the negative electrode material has a cycle life of more than 90% for 1230 weeks, indicating that the modified sodium titanate negative electrode material shows a good effect in extending the cycle life of sodium ion batteries.

[0093] The charge and discharge curves of the negative electrodes of Examples 1 to 3 and Comparative Examples 1 to 2 are as follows: Figures 1 to 5 As shown. In the preparation of sodium ion batteries, the charge and discharge curve of the electrode has good linearity, which is more conducive to detecting the SOC state of the battery, making the battery power monitoring more accurate. It can be seen from the figure that the negative electrode charge and discharge curve of the sodium ion battery using the modified sodium titanate negative electrode material has good linearity, while the negative electrode charge and discharge curve linearity of Comparative Examples 1 to 2 without using the modified sodium titanate negative electrode material is slightly worse. In addition, it can be seen from the figure that the linearity of Comparative Example 1, in which the negative electrode material is lithium titanate directly mixed into sodium titanate, is the worst, indicating that simply mixing lithium titanate into the negative electrode material cannot improve the linearity of the electrode charge and discharge curve.

[0094] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A modified sodium titanate negative electrode material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of modified sodium titanate, 40-50 parts of N-methylpyrrolidone, 3-4 parts of conductive agent, 1-2 parts of sodium carboxymethyl cellulose, 0.5-1 parts of binder, and 0.1-0.2 parts of anhydrous ethanol; The raw materials of the modified sodium titanate include: sodium titanate, lithium titanate, sodium dodecylbenzene sulfonate, octadecyl ammonium chloride, and deionized water; the particle size of the sodium titanate is not greater than 15 μm; the particle size of the lithium titanate is not greater than 5 μm; and the lithium titanate is uniformly dispersed and attached to the surface of the sodium titanate.

2. A modified sodium titanate negative electrode material according to claim 1, characterized in that: The preparation method of the modified sodium titanate is as follows: (a) At 25-30°C, sodium titanate, sodium dodecylbenzene sulfonate and deionized water are mixed and stirred in a mass ratio of 20:4-5:35-40, and then put into a high-speed ball mill. One cycle is "grinding for 1-2 minutes and resting for 10-15 seconds". After 10-12 cycles of grinding, the mixture is dried and dispersed to obtain particles A with a particle size of no more than 15 μm; (b) At 25-30° C., lithium titanate, octadecyl ammonium chloride and deionized water are mixed and stirred in a mass ratio of 20:4-5:34-38, and then put into a high-speed ball mill. One cycle is "grinding for 1-2 minutes and resting for 10-15 seconds". After 9-11 cycles of grinding, the mixture is dried and dispersed to obtain particles B with a particle size of no more than 5 μm. (c) Mixing particles A, particles B and deionized water at a mass ratio of 5-6:3-4:100 at 35-45° C., stirring at a dispersion line speed of 35-40 m / s for 40-50 min, and then drying and dispersing to obtain modified sodium titanate.

3. A modified sodium titanate negative electrode material according to claim 2, characterized in that: In step (a), the grinding rate is 700-800 r / min.

4. A sodium ion battery negative electrode containing the modified sodium titanate negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Mixing sodium carboxymethyl cellulose and N-methyl pyrrolidone at 35-55°C, stirring at a dispersion line speed of 10-20 m / s until a mixed liquid becomes clear and transparent; adding a conductive agent to the mixed liquid at 20-35°C, stirring at a dispersion line speed of 15-30 m / s for 2-5 h to obtain a primary slurry; (2) Adding modified sodium titanate material to the primary slurry at 20-35°C, stirring at a dispersion line speed of 35-40 m / s for 2.5-5.5 h, and then adding a binder and anhydrous ethanol and stirring for 1-3 h to obtain a slurry containing modified sodium titanate material; (3) The obtained slurry containing modified sodium titanate material is mixed at a rate of 100-200 g / m 2 The density is evenly coated on the current collector, and after roll pressing, the negative electrode of the sodium ion battery is obtained by die cutting.

5. A sodium ion battery negative electrode as claimed in claim 4, characterized in that: In step (2), the fineness of the slurry is not greater than 15 μm.

6. A sodium ion battery negative electrode as claimed in claim 4, characterized in that: In step (3), the material of the current collector is one of aluminum foil, copper foil and titanium foil.

7. A sodium ion battery negative electrode as claimed in claim 4, characterized in that: In step (3), the compaction density of the roller is 1.6-2.4 g / cm 3 .

8. A modified sodium titanate negative electrode material according to claim 1, characterized in that: The conductive agent is one or more of acetylene black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene.

9. A modified sodium titanate negative electrode material according to claim 1, characterized in that: The binder is one or more of polyvinylidene fluoride, sodium alginate, polyacrylic acid, polytetrafluoroethylene, acrylonitrile copolymer, polyethylene oxide, and styrene-butadiene rubber.

10. A sodium ion battery, characterized in that: The negative electrode is the negative electrode of the sodium ion battery according to any one of claims 4 to 7.

Citation Information

Patent Citations

  • A kind of preparation method of sodium titanate / graphene composite negative electrode material for sodium ion battery

    CN104600271B

  • Anode active material for sodium battery, anode, and sodium battery

    CN103931028A

  • Preparing and modifying method of cathode of sodium ion battery

    CN105428597A